TRENDS AND DETERMINANTS OF THE DEVELOPMENT OF QUALITY MANAGEMENT CONCEPTS AS AN IMPERATIVE OF THE COMPETITIVE ADVANTAGES OF THE ENTERPRISE - TELNOV, Anatoliy (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The purpose of the article is to generalize the concepts of quality management, justify the role and importance of quality management for strengthening competitive positions in the market, identify the main trends and determinants of quality management concepts in order to obtain sustainable competitive advantages of the enterprise. The article defines the content of quality management in terms of a client-oriented approach as one of the basic concepts of enterprise development in the direction of achieving competitive advantages in the market.The content of competitive advantages in the modern conditions of economic development is defined as the ability of the enterprise's aggregate potential to form and maintain a system of declared values and business principles, social responsibility of business, corporate culture of the enterprise in relation to its competitors, which satisfy the requirements of consumers and partners, and also provide the possibility of future development, taking into account instability of the market environment.The main tasks in the implementation of quality management at the enterprise have been identified. The concepts of quality management are summarized, the role and importance of quality management for strengthening competitive positions on the market is substantiated. The content of the company's quality management activities is defined, taking into account the client-oriented approach. The main trends and determinants of quality management concepts for the purpose of obtaining sustainable competitive advantages have been identified.Methods and tools of product quality management are proposed. The article provides examples of achieving product quality at enterprises, which demonstrate the diversity and business activity of enterprises in Ukraine regarding the implementation of modern concepts of quality management to achieve satisfaction of consumer needs and obtain competitive advantages. Taking into account modern trends in economic development, directions for improving quality management are proposed to obtain sustainable competitive advantages of the enterprise.
Keywords: quality; quality management; concepts; competitive advantages; client-oriented approach; determinants; mperative